KEBIJAKAN PEMERINTAH DALAM PENGELOLAAN SAMPAH DOMESTIK DI KABUPATEN BANTUL PROPINSI D.I. YOGYAKARTA - Fangga, Fangga; Mulasari, Surahma Asti (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACT Background: Garbage is a result of human activity are discarded because it was not useful, so that not all solid objects that are not used and disposed of so- called junk. Waste Management had only understood by the public sector. Waste disposed by people considered to just be the governments job alone to handle. So that the waste problem has always been a difficult problem to overcome, if it is not the role of an active community and awareness of the community it self. It is known from the data monthly report garbage in the Department of the Environment and from interviews the researchers did in June 2012 at the Department of Public Works Bantul. Number of people who throw their garbage into the existing illegal TPSS Bantul cause existing waste management can not be performed optimally and more difficult to overcome the existing problems of garbage. Based on the background above, the researcher is interested in studying